Investigated Signal-to-Noise Ratio for Terrestrial Free Space Optical based on Libya Cities Data (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Free Space Optical (FSO) communication links offer high-speed data transmission but can be affected by weather conditions like rain, haze, fog, and snow. This study investigates the impact of rain on FSO link availability in the Libyan cities of Garian, Elkhoms, and Tripoli. An empirical model based on the ITU Carb. (France) Model is proposed to predict FSO link availability for ranges up to 5 km. Rain data shows that Garian has the highest rainfall, followed by Elkhoms and Tripoli. The study examines the effects of rainfall on FSO link performance for these three cities over a 5 km link distance. The results show that signal-to-noise ratio (SNR) and received power at the FSO link are influenced by both rainfall and path length. For a 2 km link distance, the SNR ranges from 16 dB in Tripoli to 10 dB in Garian. Under the influence of rain, the SNR varies from 45 dB to 5 dB over a link distance of 1 km to 5 km.